Modern Methods of Treatment of Complications after Septoplasty - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
Removal of deviated nasal septum called septoplasty. This operation helps the patient breathe normally and naturally. But, unfortunately, many people try to keep it safe and continue to live with its deviation, which creates other damage. What worries people before surgery: Technologies have also been created that allow the patient to avoid unpleasant sensations and breathe through the nose during rehabilitation. Intranasal septal splints or splints are created according to Reiter. They are made of soft silicone, because it does not harm the nasal cavity and is removed painlessly. The splints have a seven-sided shape and completely correspond to the shape of the nasal septum at the site of operation. The essence of splints is that they hold the septum in the midline. After the operation, when the patient is under anesthesia, a silicone splint is sewn.